Diagnostic Validity of Orthopantomogram Compared to Dual Energy X-ray Absorptiometry Scan in Detecting Osteoporosis - D. Prasanna Kumar; S. Jayachandran; N. Thilagavathy (Annals of the National Academy of Medical Sciences (India), 2021)
Introduction Osteoporosis is one of the most common and rampant metabolic bone disorders among the geriatric, particularly affecting postmenopausal women. Even though resorption tends to occur more rapidly in bones with a higher proportion of trabecular bone (e.g., vertebrae, pelvis, calcaneus), bones with significant cortical bone content also do undergo resorption, for example, mandible. The dental manifestations that may indicate low-bone density include loose teeth, receding gums, and ill-fitting or loose dentures. Objective To validate the efficacy of orthopantomograms (OPGs) in recognizing bone mineral density (BMD) changes of the mandible using mandibular cortical index (MCI) and substantiate the same with dual energy X-ray absorptiometry (DEXA) scan on femoral neck and spine. Materials and Methods This cross-sectional study comprised 60 geriatric patients of both genders. All the patients were subjected to panoramic radiographs wherever clinically indicated. The visual analysis was done based on the radiographic appearance of the mandibular cortical border and results were compared with DEXA scan reports, followed by an analysis of three grades of MCI and BMD statistically. Results In our study, out of 40 patients in C2 and C3 subgroups, 67% and 20% were normal, respectively. The incidence of osteopenia was 33% in the C2 group and 70% in the C3 group, whereas Osteoporosis was present only among 10% of the population in the C3 group. The difference between the groups are statistically significant (p = 0.01). These findings imply that a progressive link exists between BMD and deteriorating cortical morphology. Conclusion The purpose of this study is that dentists will be able to refer patients to physicians of suspected low BMD, based on incidental findings on panoramic radiographs for further examination. There is a statistically significant correlation present between DEXA and MCI, so the latter can also be used for screening BMD changes.